Implementation of the Lean Construction Methodology in the Management of the Material Transportation Process- A Review - Iparraguirre-Villanueva, Orlando (2023)
One of the biggest problems in the construction industry that often generates delays and loss of value in the construction site are the processes related to the management of material transportation. These processes are decisive in collaborating in the search for greater productivity. Lean Construction (LC), together with its tools and techniques, is a methodology that is being implemented in the sector and whose objective is the identification and elimination of waste on-site.The objective of this work is to analyze the impact of implementing the LC methodology in the construction sector focused on the transportation of materials, as well as to verify the other benefits of the methodology. In this systematic literature review (SLR) work, seven online databases were used to search for scientific manuscripts related to the LC methodology and the materials transportation process; after being analyzed and systematized using the prism methodology and the inclusion and exclusion criteria, 54 manuscripts were selected, seeking to answer the research questions. The results indicate that 21 manuscripts state that the benefits provided by the application and execution of LC are fundamental to ensure the execution and success of the project. Also, LC tools and techniques are essential to improve productivity. Also, the analysis shows that the main challenges are lack of management commitment, lack of willingness to change the culture, lack of skills and lack of training. Finally, the importance of management in the building materials supply chain is demonstrated by identifying the drivers and enablers.